Why the Japanese lost : the red sun's setting - Perrett, Bryan (Pen & Sword Military, 2014)
"This book tells the story of a war unlike any other in history, fought between a nation that believed itself to be invincible, even when its strength was being systematically destroyed by the greatest industrial power in the world. Prior to the middle of the nineteenth century, the Empire of Japan was content to remain in medieval isolation and, apart from very limited trading concessions, was unwilling to extend her contacts with the western world. This was all to change however, as Japan hurtled forwards into the twentieth century, armed and determined to carve out a new identity characterised by a dominating spirit. Dejected by the Great Depression of the early 1930s, they were a nation grown from moderate to militant. Following the pivotal and devastating attack on Pearl Harbour in 1941, the Japanese Army were emboldened. Hong Kong, Malaya, Singapore, Burma, the Philippines and the Dutch East Indies were all overrun with deceptive ease, leading the army to become dangerously confident in their ability. Subsequently named 'The Victory Disease', the author argues that it was this arrogant complacency that led to the army's ultimate downfall. Each episode of note in the history of the Japanese military forces is relayed, as the author dissects, analyses and endeavours to explain the root causes and pivotal decisions that led to defeat."--Jacket